Synthesis, characterization and screening of antimicrobial, antituberculosis, antiviral and anticancer activity of novel 1,3-thiazolidine-4-ones derived from 1-[2-(benzoylamino)-4-(methylthio)butyryl]-4-alkyl/arylalkyl thiosemicarbazides - (:unkn) unknown (ARKAT USA INC, 2008)
1,3-Thiazolidine-4-ones have been known to possess miscellaneous pharmacological activities such as antibacterial, antimycobacterial, antiviral, anticancer and anticonvulsant. Therefore, we synthesized some novel 1-[2-(benzoylamino)-4-(methylthio)butyryl]-4-alkyl/aryl alkyl thiosemicarbazides, N-{1-[[2-(3-Alkyl/arylalkyl-4-oxo-1,3-thiazolidin-2-ylidene) hydrazino] carbonyl-3-(methylthio)propyl}benzamides and N-{1-[[2-[5-benzylidene)-3-alkyl/arylalkyl-4-oxo- 1,3-thiazolidin-2-ylidene]hydrazino]carbonyl-3-(methyl-thio)propyl}-benzamide derivatives. Structures of the synthesized compounds were elucidated by IR, H-1- / C-13- NMR and HR-MS spectral data. All of the compounds were tested for antibacterial and antituberculosis activity and some of the compounds exhibited marginal activity against Staphylococcus aureus ATCC 29213, Bacillus subtilis A57 and Candida albicans A177. Antiviral activity of the synthesized compounds was determined against various types of viruses in HEL, HeLa and Vero cell cultures. Anti-HIV and cytotoxicity data were also obtained with the compounds using the strains HIV-1 (IIIB) and HIV-2 (ROD) in an MT-4/MTT based assay. None of the tested compounds showed antiviral activity at subtoxic doses whereas some of them exhibited remarkable cytotoxic potential. Target compounds were also screened for their antituberculosis potency against Mycobacterium tuberculosis H37 Rv, and some of them showed varying degrees of inhibition. Among the compounds tested, compound 27 was found to be most potent with 90% inhibition of mycobacterial growth at 6.25 mu g/ml. Compounds 8, 13, 14, 23, 25 were evaluated for their anticancer activity by the National Cancer Institute (NCI).
Keywords: 4-Thiazolidinones; methionine; antituberculosis activity; antiviral activity; anti-cancer activity; NATIONAL-CANCER-INSTITUTE; MYCOBACTERIUM-TUBERCULOSIS; DRUG DISCOVERY; HIV; DERIVATIVES; 4-THIAZOLIDINONES; INHIBITORS; DESIGN; 2,3-DIARYL-1,3-THIAZOLIDIN-4-ONES; 1,3,4-OXADIAZOLES